In Search of Metropolitan Definitions: Lessons from Metro Davao - Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1998)
Angotti has suggested a rule of thumb in defining a metropolis or distinguishing it from a city. While city refers to medium-sized settlements between 100 000 to 1 million, metropolis refers to large urban settlements with at least a million populations. In addition, metropolis is coined to areas undertaking metropolitan functions/activities, which are distinctly urban in nature and dimension and which need institutional mechanism when one or more political jurisdictions are involved. This paper attempts to describe three emerging operational definitions of Metro Davao by presenting definitional dilemma. More importantly, it draws insights on the importance of definitions beyond the terminological exercise.
Keywords: 330; metropolitan structure; Davao Integrated Development Program; metropolitan planning and development